'There is nothing more practical than a good theory': Conceptual tools for conservation practice. (1st June 2016) - Verbeeck, Muriel
Abstract : Faced with the growing number of case studies in contemporary art, philosophy provides conservators with a series of conceptual tools that allow to theorize their practice. The notion of intentionality and attentionality borrowed from Genette enables a better understanding of the problems that Dirty Corner by Anish Kapoor (a work vandalized on many occasions) poses. I will show that the conservator deals with the issue of the identity of a contemporary work in a different way from the art historian, and that philosophy is a practical tool to understand the specificity of the former's approach and intervention.